Best before? Expiring central bank digital currency and loss recovery - Charles M. Kahn; Maarten R. C. Van Oordt; Yu Zhu (Bank of Canada, 2021)
An important feature of physical cash payments is resilience, which is due to their indifference to power outages or network coverage. Many central banks are exploring issuing digital cash substitutes with similar online payment functionality. Such substitutes could incorporate novel features, making them more desirable than physical cash. This paper considers introducing an expiry date for online digital currency balances to automate personal loss recovery. We show that this functionality could substantially increase consumer demand for digital cash, with the time to expiration playing an important role. Having more information available to the central bank improves accuracy of loss recovery but may decrease welfare.
Keywords: E41; E42; 330; Digital currencies and fintech